Recombination between non-structural and structural genes as a mechanism of selection in lagoviruses: The evolutionary dead-end of an RHDV2 isolated from European hare - Cavadini, Patrizia; Trogu, Tiziana; Velarde, Roser; Lavazza, Antonio; Capucci, Lorenzo (Virus research, 2024)
•RHDV2_Bg12 originated in a hare through recombination at the RdP-VP60 junction.•Structural genes come from RHDV2, the non-structural ones from a new hare lagovirus.•Rabbits orally inoculated with RHDV2_Bg12 neither developed RHD nor seroconverted.•RHDV2_Bg12 has no longer been identified despite active surveillance on lagomorphs. The genus Lagovirus, belonging to the family Caliciviridae, emerged around the 1980s. It includes highly pathogenic species, rabbit hemorrhagic disease virus (RHDV/GI.1) and European brown hare syndrome virus (EBHSV/GII.1), which cause fatal hepatitis, and nonpathogenic viruses with enteric tropism, rabbit calicivirus (RCV/GI.3,4) and hare calicivirus (HaCV/GII.2). Lagoviruses have evolved along two independent genetic lineages: GI (RHDV and RCV) in rabbits and GII (EBHSV and HaCV) in hares. To be emphasized is that genomes of lagoviruses, like other caliciviruses, are highly conserved at RdRp-VP60 junctions, favoring intergenotypic recombination events at this point. The recombination between an RCV (genotype GI.3), donor of non-structural (NS) genes, and an unknown virus, donor of structural (S) genes, likely led to the emergence of a new lagovirus in the European rabbit, called RHDV type 2 (GI.2), identified in Europe in 2010. New RHDV2 intergenotypic recombinants isolated in rabbits in Europe and Australia originated from similar events between RHDV2 (GI.2) and RHDV (GI.1) or RCV (GI.3,4). RHDV2 (GI.2) rapidly spread worldwide, replacing RHDV and showing several lagomorph species as secondary hosts. The recombination events in RHDV2 viruses have led to a number of viruses with very different combinations of NS and S genes. Recombinant RHDV2 with NS genes from hare lineage (GII) was recently identified in the European hare. This study investigated the first RHDV2 (GI.2) identified in Italy in European hare (RHDV2_Bg12), demonstrating that it was a new virus that originated from the recombination between RHDV2, as an S-gene donor and a hare lagovirus, not yet identified but presumably nonpathogenic, as an NS gene donor. When rabbits were inoculated with RHDV2_Bg12, neither deaths nor seroconversions were recorded, demonstrating that RHDV2_Bg12 cannot infect the rabbit. Furthermore, despite intensive and continuous field surveillance, RHDV2_Bg12 has never again been identified in either hares or rabbits in Italy or elsewhere. This result showed that the host specificity of lagoviruses can depend not only on S genes, as expected until today, but potentially also on some species-specific NS gene sequences. Therefore, because RHDV2 (GI.2) infects several lagomorphs, which in turn probably harbor several specific nonpathogenic lagoviruses, the possibility of new speciation, especially in those other than rabbits, is real. RHDV2 Bg_12 demonstrated this, although the attempt apparently failed.